Assessing the impact of smart cities on local E-government research: a bibliometric study - Dias, Gonçalo Paiva (2020)
This article contributes to the knowledge body by establishing the current situation in terms of need, adoption and advertising of privacy policies in the Web sites of Portuguese local authorities, and by collecting evidence of its compliance with privacy practices. Web sites of all the 308 Portuguese municipalities were surveyed for the presence of privacy policies, the usage of tracking cookies and measures taken to secure user credentials. A conceptual analysis was performed on privacy policies to categorize their content. Results were compared with other international studies. It was found that only 26% of the municipalities provide privacy policy statements and many of those exhibit significant gaps considering the information that can be expected in such documents. Furthermore, evidence of non-compliance with the advertised privacy policies and the legislation was also collected. The presented conclusions are useful for both academics and practitioners in the areas of e-government, privacy assurance and local government.